Differences in Development of Gross Motor and Fine Motor Skills of Stunting and Non-Stunting Toddlers Aged 36-59 Months - Astuti Nur; Juni Gressilda L Sine Sine; Maria Helena Dua Nita (Sarana Ilmu Indonesia (salnesia), 2022)
Stunting is a chronic malnutrition condition that has an impact on children's brain development. This study aimed to determine the differences in gross motor and fine motor skills development of toddlers aged 36-59 months between stunting and non-stunted in Kupang City. The type of research utilized was an analytical observation by cross-sectional design. The population was all children receiving Early Childhood Education (PAUD) in Kupang City, as many as 8580 children. The study was carried out in January-May 2022. The sampling technique used random cluster sampling to obtain a sample of 382 children. Nutritional status was obtained using the TB/U indicator. The motor development of toddlers was obtained through the Denver II test. The statistical test used is the chi-square test. The results showed that 22% of toddlers were classified as stunting, 6,8% of toddlers with gross motor skills were classified as suspect, and 36,1% of toddlers with fine motor skills were classified as suspicious (dubious development/failure to test). There were differences in gross and fine motorik development in stunted and non-stunted toddlers with p<0,05. PAUD Managers are expected to be more active in monitoring early childhood growth and development, especially in stunted children. If deviations are discovered or suspected, immediate action can be taken to ensure that growth and development are not disrupted.